THE INFLUENCE OF FINANCIAL LITERACY AND FINANCIAL TECHNOLOGY ON GENERATION Z INVESTMENT DECISIONS (CASE STUDY OF MANAGEMENT STUDENTS OF BANDAR LAMPUNG UNIVERSITY CLASS OF 2020) - Oktaviani; Habiburahman (International Journal of Accounting, Management, Economics and Social Sciences (IJAMESC), 2024)
With an asset value of IDR 144.07 trillion at the end of the first semester of 2022, stock investors under 40 years old, namely gen Z and millennials by 81.64 percent. Most investors, 60.45%, work as private employees, civil servants, teachers, and students, with an asset value of Rp358.53 trillion. Demographic data shows that the majority of stock investors live on the island of Java, including 13.97% of those living in DKI Jakarta, with an asset value of Rp3,772.32 trillion. While the island of Sumatra is only 16.62%. From the explanation above, we can conclude that there is still low investment interest in several regions, especially Sumatra. The research problems are: Can financial literacy affect investment decisions in generation z in Bandar Lampung city, whether there is an influence between financial technology on investment decisions in generation z in Bandar Lampung city, whether financial literacy and financial technology can affect investment decisions in generation z in Bandar Lampung city.The purpose of this study is to determine the influence of financial literacy and financial technology towards investment decisions in generation z in Bandar Lampung city. Based on the results of the t test, it shows that the value of t calculated for Financial Literacy is greater than t table (3.687 > 1.998), and the value of sig = 0.006 < 0.05. In multiple regression analysis, financial literacy has a positive value for investment decisions. Financial technology has a positive and significant influence on the investment decisions of students or generation Z in the city of Bandar Lampung, meaning that the hypothesis is accepted. The results of the t test show that the value of t calculated by Financial Technology is greater than t table (2.515 > 1.998). In multiple regression analysis, financial technology has a positive value for investment decisions. The results of processing and analysis show that financial literacy and financial technology have a positive and significant impact on the investment decisions of generation Z in Bandar Lampung.